Overexpression of the transcription factors OCT4 and KLF4 improves motor function after spinal cord injury. (25th May 2020) - Huang, Xianpeng; Wang, Chenggui; Zhou, Xiaopeng; Wang, Jingkai; Xia, Kaishun; Yang, Biao; Gong, Zhe; Ying, Liwei; Yu, Chao; Shi, Kesi; Shu, Jiawei; Cheng, Feng; et al.
Abstract: Introduction: Astrogliosis and glial scar formation following spinal cord injury (SCI) are viewed as major obstacles that hinder axonal regeneration and functional recovery. Regulating the glial scar and axonal regeneration in the lesion site is important for treating SCI. Aims: Considering the important role of astrocyte in glial scar formation and subsequent axonal regeneration, we intended to investigate the effect of the transcription factors OCT4 and KLF4 on astrocyte and the underlying mechanism after spinal cord contusion injury in transgenic mice. Results: Western blotting, q‐PCR, immunofluorescence, and functional evaluation suggested that glial fibrillary acidic protein (GFAP) expression decreased in the lesion area, the porosity of the scar increased, and remyelination enhanced. Mice overexpressing the transcription factors OCT4 and KLF4 had higher Basso Mouse Scale scores than did the control mice. Moreover, using immunofluorescence and Western blotting, we discovered that some astrocytes expressed nestin and sox2 protein, suggesting that these astrocytes were reprogrammed into neural stem cell‐like cells. Furthermore, a cell scratch assay showed that the migration ability of the astrocytes was significantly inhibited in the presence of the transcription factors OCT4 and KLF4. In addition, we demonstrated that the Hippo/Yap pathway was activated after these two transcription factors overexpressed in astrocytes. Conclusions: In summary, these results suggest that overexpression of the transcription factors OCT4 and KLF4 could induce astrocyte reprogramming, which subsequently improves remyelination and functional recovery after SCI.